Comparison of plaque control record measurements obtained using intraoral scanner and direct visualization - Kazuya Doi; Chihiro Yoshiga; Hiroshi Oue; Reiko Kobatake; Maiko Kawagoe; Hanako Umehara; Kaien Wakamatsu; Kazuhiro Tsuga (Wiley, 2024)
Abstract Objective Intraoral scanner (IOS) can acquire three‐dimensional color images of teeth. Thus, the detection of areas with plaque adhesion stained by plaque‐disclosing solutions using an IOS could be a potential oral hygiene evaluation method. This study aimed to verify the usefulness of obtaining O'Leary's plaque control record (PCR) measurements using an IOS in clinical practice. Methods Twenty patients with >20% PCR measurements who underwent oral prophylaxis were enrolled in this study. A plaque‐disclosing gel was applied to stain the areas with plaque adhesion, and the dentition was scanned using the IOS. The PCR values obtained via the direct method and those obtained using the digital image were compared for the entire dentition, maxillary total area, the labial and palatal aspects of the maxillary anterior teeth, the buccal and palatal aspects of the maxillary posterior teeth, mandibular total area, the labial and lingual aspects of the mandibular anterior teeth, and the buccal and lingual aspects of the mandibular posterior teeth. Results The IOS group tended to have higher values than the direct observation group. The labial and palatal aspect of the maxillary anterior teeth, the labial and lingual aspects of the mandibular anterior teeth did not differ significantly between the groups. Conclusion Plaque adhesion was visualized easily and conclusively using an IOS. As the large tip size often hinders its use, it is necessary to develop a smaller IOS tip in the future.